Void structures in olivine grains in thermally metamorphosed Antarctic carbonaceous chondrite B-7904 - Akai, Junji (National Institute of Polar Research, 1994)
P(論文) The Antarctic carbonaceous chondrite Belgica-7904 suffered thermal metamorphism. The main constituent phyllosilicates of this meteorite are serpentine and/or saponite, which display transformation from serpentine to olivine or from saponite to enstatite in various degrees (J. AKAI : Geochim. Cosmochim. Acta, 52,1593,1988; Proc. NIPR Symp. Antarct. Meteorites, 3,55,1990). Detailed Transmission Electron Microscopy (TEM) observation of this meteorite reveals characteristic void structures, which are found mainly in olivine grains. The voids or bubble-like structures are very frequently found in some grains. The shapes of the voids are varied. Some are irregular and some are crystallographically controlled. Five possible mechanisms for their origin are : 1) thermal metamorphism, 2) irradiation by high energy particles in the solar nebula, 3) shock effects, 4) sample preparation artifacts and 5) alteration process. Among five or more possible mechanisms, the voids mostly likely formed during thermal metamorphism or as a result of irradiation damages by high energy particles in the early solar system. departmental bulletin paper